UK long-term monitoring dataset: assessing factors affecting biomarkers commonly used in environmental programmes - Dalessandri, Shannon; Franco, Aldina M. A.; Assunção, Marta G. L. (Frontiers in Marine Science, 2023)
Long-term programmes like the UK Clean Seas Environmental Monitoring Programme (CSEMP) rely on biological effects techniques, including biomarkers, to assess if chemical pollutants are affecting sentinel species in the aquatic environment. In this study, we have applied mixed and fixed effect linear models to the long-term CSEMP dataset (2005-2018) to evaluate if factors such as region (location), sex, age, gonadosomatic index (GSI) and condition factor (CF), contribute to the variability observed in the levels of 3 well established biomarkers (inhibition of acetylcholinesterase in muscle-AChE, induction of hepatic 7-ethoxyresorufin-O-deethylase-EROD and presence of biliary 1-hydroxypyrene-1-OH pyrene) used to monitor biological effects of contaminants in dab (Limanda limanda) around UK waters. Regional differences (location) were a significant explanatory variable for the 3 biomarkers. Substantial differences were found in regional average muscle AChE activity, overall indicating the East Coast regions as likely more impacted by acetylcholinesterase inhibitors (e.g. organophosphates and carbamates). We report for the first time that, while accounting for region, sex and gonadosomatic index are significant predictors of muscle Acetylcholinesterase isoform in dab (R2=0.13-0.15), and therefore advise the future analysis of this marker should be done by sex when reporting for marine environmental purposes. Dab condition factor is also a significant predictor for both enzymatic markers (AChE and EROD) but not for 1-OH pyrene. Sex and age, and their interaction, were the strongest variables (R2=0.46) influencing hepatic EROD, showing that although overall females had higher hepatic EROD, male dab hepatic EROD increased with age. Correlations between the three biomarkers might assist in discerning types of prevalent regional contamination over the studied period. Our results highlight the factors to account for when assessing if environmental contamination is contributing to the responses of these 3 biomarkers in dab, and other flatfish species, used in marine environmental monitoring programmes.